Household sanitation and personal hygiene practices are associated with child stunting in rural India: a cross-sectional analysis of surveys. Issue 2 (12th February 2015) - Rah, Jee Hyun; Cronin, Aidan A; Badgaiyan, Bhupendra; Aguayo, Victor M; Coates, Suzanne; Ahmed, Sarah
Abstract : Objectives: Increasing evidence suggests that water, sanitation and hygiene (WASH) practices affect linear growth in early childhood. We determined the association between household access to water, sanitation and personal hygiene practices with stunting among children aged 0–23 months in rural India. Setting: India. Participants: A total of 10 364, 34 639 and 1282 under-2s who participated in the 2005–2006 National Family Health Survey (NFHS-3), the 2011 Hunger and Malnutrition Survey (HUNGaMA) and the 2012 Comprehensive Nutrition Survey in Maharashtra (CNSM), respectively, were included in the analysis. Primary outcome measures: The association between WASH indicators and child stunting was assessed using logistic regression models. Results: The prevalence of stunting ranged from 25% to 50% across the three studies. Compared with open defecation, household access to toilet facility was associated with a 16–39% reduced odds of stunting among children aged 0–23 months, after adjusting for all potential confounders (NHFS-3 (OR=0.84, 95% CI 0.71 to 0.99); HUNGaMA (OR=0.84, 95% CI 0.78 to 0.91); CNSM (OR=0.61, 95% CI 0.44 to 0.85)). Household access to improved water supply or piped water was not in itself associated with stunting. The caregiver's self-reported practices of washing hands with soap before meals (OR=0.85, 95% CI 0.76 to 0.94) or after defecation (OR=0.86, 95% CI 0.80 to 0.93) were inversely associated with child stunting. However, the inverse association between reported personal hygiene practices and stunting was stronger among households with access to toilet facility or piped water (all interaction terms, p<0.05). Conclusions: Improved conditions of sanitation and hygiene practices are associated with reduced prevalence of stunting in rural India. Policies and programming aiming to address child stunting should encompass WASH interventions, thus shifting the emphasis from nutrition-specific to nutrition-sensitive programming. Future randomised trials are warranted to validate the causal association.